Pengembangan E-Modul Teks Cerita Fantasi Bermuatan Bernalar Kritis Berbasis Flipbook - Syahraini Nursyifa Camila; Lutfi Syauki Faznur (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
This research is motivated by the difficulties experienced by students in imagining and composing fantasy stories. To overcome this, a Flipbook-based e-module was developed for the Indonesian Language subject with fantasy story text material containing elements of critical reasoning to train students' critical reasoning skills. The purpose of this research is to develop digital learning media that facilitates the learning process. The research uses the ADDIE development model (analysis, design, development, implementation, evaluation). This research was conducted at Puspita Middle School with 39 students of class VII-G as research subjects. Data were collected through observation, interviews, and questionnaires to students, educators, media experts and material experts to assess the feasibility of the e-module. The results showed that the e-module was declared valid and practical to use, with an assessment from media experts of 86.67%, material experts 98.67%, indicating a statement that it was very appropriate without revision, and an assessment from Indonesian Language teachers of 94.67%, and student responses of 96.14%. Thus, the e-module of fantasy story texts containing critical reasoning based on flipbooks gets a very good and very decent category.